2013
DOI: 10.1002/pola.26519
|View full text |Cite
|
Sign up to set email alerts
|

“Nascent” Cu(0) nanoparticles‐mediated single electron transfer living radical polymerization of acrylonitrile at ambient temperature

Abstract: Zn(0)/ppm concentrations of CuBr2 from 10 to 50 ppm was firstly used to catalyze radical polymerization of acrylonitrile at ambient temperature. The polymerization displayed typical living radical polymerization (LRP) characteristics, as evidenced by pseudo first‐order kinetics of polymerization, linear increase of number‐average molecular weight, and low polydispersity index (PDI) value. Effects of solvent, copper concentration, and initiator concentration on the polymerization reaction and molecular weight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
0
12
2
Order By: Relevance
“…5), there is a peak shi to higher molecular weight aer the extended chain of PMMA (M n , GPC ¼ 76 566 g (Table 1d). Cheng et al 30 observed that there was no polymerization occurred when the concentration of Cu(0) decreases to 2.5 ppm but in the present study, we observed polymerization with monomer conversion of 25 wt% and Đ 1.29 at 0.15 ppm of Cu(0) nanoparticles concentration (Table 1e). Overall by using Cu(0) nanoparticles of 5 nm, polymerization is very fast with good conversion of monomer by using PMDETA and TMHDA as ligands.…”
Section: Chain End Functionality and Chain Extensioncontrasting
confidence: 57%
See 2 more Smart Citations
“…5), there is a peak shi to higher molecular weight aer the extended chain of PMMA (M n , GPC ¼ 76 566 g (Table 1d). Cheng et al 30 observed that there was no polymerization occurred when the concentration of Cu(0) decreases to 2.5 ppm but in the present study, we observed polymerization with monomer conversion of 25 wt% and Đ 1.29 at 0.15 ppm of Cu(0) nanoparticles concentration (Table 1e). Overall by using Cu(0) nanoparticles of 5 nm, polymerization is very fast with good conversion of monomer by using PMDETA and TMHDA as ligands.…”
Section: Chain End Functionality and Chain Extensioncontrasting
confidence: 57%
“…Similar trend was observed when concentration of Cu(0) nanoparticles reduced to 0.75 ppm (Table 1d). Cheng et al 30 observed that there was no polymerization occurred when the concentration of Cu(0) decreases to 2.5 ppm but in the present study, polymerization with monomer conversion of 25 wt% and dispersity (Đ) 1.29 at 0.15 ppm of Cu(0) nanoparticles concentration (entry 1, Table 1e) was observed. Overall by using Cu(0) nanoparticles The results shows that the molecular weight of PMMA increases linearly with conversion, whereas, polydispersity decreases from 1.6 to 1.4 with increasing conversion at 25 C (Fig.…”
Section: Synthesis Of Cu(0) Nanoparticlescontrasting
confidence: 56%
See 1 more Smart Citation
“…Procedures employing lower catalyst concentrations for PAN synthesis, including activators regenerated by electron transfer (ARGET), initiators for continuous activator regeneration (ICAR), and supplemental activators and reducing agents (SARA) ATRP were previously used. For example, the synthesis of PAN by ARGET ATRP resulted in high MW PAN ( M n = 161,300) with a narrow MWD ( M w / M n = 1.18) .…”
Section: Introductionmentioning
confidence: 99%
“…To further follow the polymerization kinetics as well as the evolutions of the molecular weight and molecular weight distributions, the polymerizations of MMA and St mediated by NaH 2 PO 2 ·H 2 O/CuSO 4 ·5H 2 O in DMSO at 25°C were investigated in more detail (Figures and ). Obviously, the polymerization kinetics curves of MMA (Figure a) and St (Figure a) are of first order in monomer conversions, implying the constant radical concentration throughout the polymerization . Moreover, the reactions display rapid rates of polymerizations.…”
Section: Resultsmentioning
confidence: 96%